THE IMPORTANCE OF THE HEURISTIC METHOD IN THE FORMATION OF PROFESSIONAL COMPETENCE OF FUTURE PEDAGOGICAL EDUCATORS IN THE CONDITIONS OF THE NEW UZBEKISTAN - Israilova Navruza Abdulhamid daughter (Bright Mind Publishing, 2025)
This article provides information on the types, structure, pedagogical functions, directions and possibilities of using heuristic tasks to help future teachers develop their professional competences. Specific recommendations are also provided for the use of heuristic tasks, learning materials used in heuristic education, learning process design, reflection and prediction, mental activities, and creative thinking.
Keywords: Future teacher, heuristic assignments, heuristic education, professional competencies, professional knowledge, pedagogical function, heuristic approach, didactic tools, methods.